The optimal substrate choice for effective biosensors based on THz metasurfaces - Pradeep Tiwari; Deepak Kala; Maciej Sakowicz (Scientific Reports)
Abstract This article explores the impact of substrate choice on the sensitivity of sensors that utilize metallic terahertz metasurfaces as the actuating element. While terahertz metasurfaces represent a rapidly evolving field, fundamental research remains essential and highly impactful. A critical component of any metasurface is the dielectric substrate on which it is fabricated – a factor that holds significance across all spectral ranges. This work focuses specifically on metallic terahertz metasurfaces operating in transmission mode. It provides an overview of various substrates (Ge, Si, SiO₂, TPX) and discusses design principles for such metasurfaces, including magnetic and electric dipole surface plasmon resonances, Fano resonances, and quasi-bound states in the continuum. We initially simulated the structures using COMSOL Multiphysics software and then confirmed the results experimentally by detecting various concentrations of bovine serum albumin. Our study systematically examines how real-metal modeling and substrate selection influence the Q-factor and sensing performance, in contrast to earlier research that either fixed the substrate type or modeled the metal as a perfect electric conductor. This dual approach provides valuable guidance for designing high-Q, low-loss terahertz metasurface biosensors. Our results demonstrate that for all types of terahertz metasurfaces operating in transmission mode, using a low-refractive-index substrate enhances sensor sensitivity, making it the preferred choice for sensing applications. This opens new prospects for the design of high-sensitivity biosensors.